Farm exit, wellbeing and autonomy: a quantitative analysis of exited farmers in Australia. Issue 2 (4th May 2019) - Peel, Dominic; Schirmer, Jacki; Berry, Helen; O'Brien, Lean Veronica
ABSTRACT: In many developed countries, the number of farmers working in commercial agriculture continues to decline with more likely to leave in the future. The act of farming and autonomy of farming work are central to farmers' identity. Although loss of autonomy when exiting farming may pose a threat to identity and reduce farmer wellbeing, these are notable gaps in existing social research. This article retrospectively examines farmer autonomy and wellbeing in a sample of 412 Australian exited farmers. Regression modelling showed those who reported lost autonomy when leaving farming reported consistently lower levels of wellbeing than those who did not lose autonomy. Supports that assist farmers to maintain their autonomy during and after exiting the occupation may help to protect against stresses associated with farm exit and improve wellbeing outcomes for exited farmers.